Ursolic acid ameliorates CCl4‐induced liver fibrosis through the NOXs/ROS pathway. Issue 10 (19th April 2018) - Gan, Dakai; Zhang, Wang; Huang, Chenkai; Chen, Jiang; He, Wenhua; Wang, Anjiang; Li, Bimin; Zhu, Xuan
Abstract : Liver fibrosis is a reversible wound‐healing response that occurs after liver injury. NADPH oxidases (NOXs) and reactive oxygen species (ROS) which are expressed in hepatocytes (HCs), hepatic stellate cells (HSCs), and Kupffer cells (KCs) play an important role in the development of hepatic fibrosis. In in vitro studies, we had shown that ursolic acid (UA) could reverse liver fibrosis by inhibiting the activation of NOX‐mediated fibrotic signaling networks in HSCs. In this study, we verified that UA could alleviate CCl4‐induced liver fibrosis by reducing the expression of NOXs/ROS in HCs, HSCs, KCs. Meanwhile, the phagocytic index α and clearance index K which represent phagocytosis of KCs were unchanged. Together, all our data demonstrated that UA induced the proliferation of HCs, promoted apoptosis in HSCs, and prevented activation of KCs in vivo by reducing the expression of NOXs/ROS in HCs, HSCs, KCs. Besides, UA had no effect on the host defense function. Abstract : UA induces the proliferation of HCs, promotes the apoptosis of HSCs, and prevents the activation of KCs in vivo by reducing the expression of NOXs/ROS in HCs, HSCs, KCs. UA also partly improves phagocytosis of KCs and has no effect on host defense function.